Pharmacokinetics, Pharmacodynamics, and Safety of MEDI4212, an Anti-IgE Monoclonal Antibody, in Subjects with Atopy: A Phase I Study. Issue 2 (February 2016) - Sheldon, Eric; Schwickart, Martin; Li, Jing; Kim, Keunpyo; Crouch, Sarah; Parveen, Shaista; Kell, Chris; Birrell, Claire
Abstract Introduction The anti-IgE therapy omalizumab is currently licensed for the treatment of moderate to severe allergic asthma and chronic idiopathic urticaria. Owing to limitations in the use of omalizumab, a need exists for optimized anti-IgE therapies to broaden clinical indications and patient populations, and to improve dosing schedules. The objective of this phase I, randomized, placebo/omalizumab-controlled, first-in-human, dose-escalation study was to evaluate the pharmacokinetics, pharmacodynamics, and safety of the high-affinity, anti-IgE therapy MEDI4212 in non-Japanese and Japanese subjects with atopy and/or diagnostic IgE ≥30 IU/mL. Methods Subjects with atopy and/or baseline IgE ≥30 IU/mL were randomized to a single dose of subcutaneous (5, 15, 60, 150, or 300 mg) or intravenous (300 mg) MEDI4212, subcutaneous omalizumab, or placebo. Following administration, pharmacokinetic, pharmacodynamic [IgE (free and total), and cellular FcεRI expression], and safety assessments were made. Results MEDI4212 rapidly suppressed free serum IgE to a greater extent than omalizumab; however, recovery of free IgE to baseline in MEDI4212-dosed subjects was rapid when compared with the slow and gradual recovery seen in omalizumab-dosed individuals. The loss of IgE suppression corresponded with a rapid decrease of serum MEDI4212. FcεRI expression on dendritic cells and basophils was reduced following MEDI4212 dosing. MEDI4212 was well tolerated by subjects; adverse events were generally of low severity and no subjects discontinued due to adverse events. Conclusions The increased potency of MEDI4212 may be of clinical interest for individuals with high-diagnostic IgE levels where more extensive IgE suppression is required for clinical response. However, the modest duration of free IgE suppression below the target concentration noted with MEDI4212 in this study suggests limited potential for dosing schedule advantages over omalizumab. Funding MedImmune. Trial registration ClinicalTrials.gov identifier, NCT01544348.